Neon Fluid Tree: Bio-Artificial Trees in Urban Landscape and Weather Detecting Systems - Bunga Shafira Muthmainah; Disha As Syifa Maharani; Siti Chairun Nabila; Hendri Hendri; Afryansyah Afryansyah (Jurnal Penelitian Medan Agama, 2025)
Urban air pollution continues to worsen due to high vehicle emissions, limited green spaces, and the declining ability of vegetation to absorb carbon dioxide. To address this, this study proposes the Neon Fluid Tree, a portable bio-artificial system leveraging Chlorella microalgae to enhance CO₂ absorption and oxygen production in urban settings. Microalgae are known for efficient carbon fixation via photosynthesis, and photobioreactor cultivation systems have improved CO₂ mass transfer and fixation performance. Studies have shown that Chlorella vulgaris can absorb CO₂ at significant rates in controlled systems, with values up to ~0.255 g CO₂ per liter per day under optimized conditions. Moreover, enhanced CO₂ uptake can be achieved through improved reactor designs and mass transfer methods, significantly increasing CO₂ utilization efficiency. Transcriptomic analyses reveal that Chlorella adapts its carbon fixation pathways in response to elevated CO₂, indicating its suitability for high-CO₂ environments. Overall, these findings support the potential of Chlorella-based systems like the Neon Fluid Tree for compact, high-efficiency urban air quality improvement. Carbon dioxide levels and strengthening urban environmental resilience.